How Does Mode of Qualitative Data Collection Affect Data and Cost? Findings from a Quasi-experimental Study. Issue 1 (February 2020) - Namey, Emily; Guest, Greg; O'Regan, Amy; Godwin, Christine L.; Taylor, Jamilah; Martinez, Andres
Internet-based platforms are increasingly used to collect qualitative data. We conducted a quasi-experimental study to explore whether data collection mode affects data content and data collection costs. Participants ( N = 171) were assigned systematically to one of four modes—(1) in-person (control), (2) online video–based, (3) online chat–based, (4) online e-mail/message board-based—and randomized to individual interview (IDI) or focus group (FG). We conducted 48 IDIs and 24 FGs about medical risk during pregnancy with women in the southeast United States. We found audiovisual (in-person and online video) modes generated significantly greater volumes of data than online text–based modes. However, there were no significant differences in the thematic content among modes, for IDIs or FGs. Online data collection generally cost more per event without travel; in-person IDIs/FGs were more expensive if including travel. Findings offer empirical data for considerations of online versus in-person qualitative data collection.